Characterization of mesoporous solids: pore condensation and sorption hysteresis phenomena in mesoporous molecular sieves. - Thommes, Matthias; et al. (Studies in Surface Science and Catalysis, 2002)
We report results of an exptl. study of pore condensation and hysteresis phenomena of nitrogen and argon in pristine MCM-48 and MCM-41 silica materials (pore diam. range: 3.5 - 5 nm). An anal. of nitrogen and argon adsorption/desorption isotherms obtained on a MCM-48 silica sample (pore diam. 4.6 nm) at 77 K and 87 K, resp., leads to the conclusion, that - although MCM-48 consists of a unique, three-dimensional pore network - the desorption branch of the argon sorption hysteresis loop (type H1) corresponds to the pore diam. However, the sorption hysteresis behavior for argon sorption at 87 K and 77 K appears to be peculiar in MCM-41 and MCM-48 materials of smaller pore diams. (i.e. in the range between 3.5 and 4.2 nm). A clear correlation between the desorption branch of the obsd. argon hysteresis loops and the pore diam. is not possible anymore in this pore diam. range. Further, a detailed comparison of the pore condensation and hysteresis behavior in MCM-48 and MCM-41 silica materials of nearly equal pore diams. reveals that sorption hysteresis loops are wider in the pseudo-one-dimensional pores of MCM-41 compared to the three-dimensional pore system of MCM-48 silica. [on SciFinder(R)]
Keywords: mesoporous mol sieve pore condensation adsorption desorption hysteresis